Book Reviews (International review of mission, 1972)
Book reviewed in this article: Old And New in Southern Shona Independent Churches. Vol. I: Background and Rise of the Major Movements. By M. L. Daneel. German Missions in Tanganyika 1891–1941: Lutherans and Moravians in the Southern Highlands. By Marcia Wright, O. U. P. Religion and the Transformation of Society: A Study in Social Change in Africa, by Monica Wilson. Anti-rassismus Programm der Ökumene: Dokumentation einer Auseinandersetzung, zusammengestellt und kommentiert von K.-M. Beckmann und mit einem Nachwort von H. Thimme, epd-dokumentation Bd. Christian and Muslim in Africa by Noel Q. King. Alive to God by Kenneth Cragg.